Our experience of buffalo improvement in India: last 50 years journey - T. K. Datta (Revista Científica)
Man has always been searching for an Elixir to free him from all suffering. Though unsure of the existence of such an elixir, India’s ancient scriptures have identified it as ‘Milk’. India’s story as the largest producer of milk is eventful. There was a phase when the country’s milk production hit an all-time low, a mere 17 million Tonnes (mT) in 1950. In 1970, with Operation Flood under the leadership of Verghese Kurien, India embarked on a journey to create history by replicating the dairy cooperatives, ushering in a transformation in the sector popularly known as the ‘white revolution.’ In 2022, India produced a record of 221 mT of milk. In India, 31.58% of the total milk production is contributed by Indigenous Buffaloes, and non-descript buffaloes contribute to 13.49% of the total milk production in the country, making it a total of 45.07% by buffaloes alone. It is well documented that buffaloes are efficient milk producers and the most preferred animal over cattle in many parts of the country owing to their superior quality of milk, disease resistance, longer productive life, and higher milk productivity. India holds the world’s largest buffalo population, with 109.85 million headcounts, constituting 20.45% of the livestock population. India has a rich genetic diversity of buffaloes with 20 registered breeds, with Murrah as the most prominent breed (42% of the total buffalo population). However, it faces challenges concerning low artificial insemination (AI) coverage (~40% of breedable females), demand gap of frozen semen doses, realized genetic gain, scarce fodder availability, and market linkages. With the small-holder farming system ( ≤ 10 cows & buffaloes/unit) being the most popular in India, the joint efforts by the Government of India, ICAR institutes such as CIRB, National Dairy institutes, and various research organizations have led to the science-driven transformation of the dairy sector. Research at ICAR-CIRB continuously emphasizes essential dimensions like genetic improvement of prominent breeds of buffalo, dissemination of high genetic merit germplasm to farmers, use of advanced reproduction biotechnologies for faster multiplication of superior germplasm, developing improved feeding modules for efficient production while reducing the methane emission and capacity enhancement of buffalo farmers, young entrepreneurs, and researchers. Alongside the dairy sector, buffaloes have a significant role in India’s meat production and export system. Total Buffalo meat production in the country is 1584.65 thousand Tonnes, which is being exported to more than 70 countries in the world. Though there are particular challenges for the overall development of buffalo production in India, the present-day progress and the future opportunities for scientific interventions through collaborative efforts have the potential to open new avenues for buffalo development and make this species the most economical food animal.